Gynecological Morbidities in Women of Reproductive Age Group in Urban Slums of Bhavnagar City - Vibha V Gosalia; Pramodkumar B Verma; Vikas G Doshi; Manindrapratap Singh; Sanat K Rathod; Mehul T Parmar (Medsci Publications, 2012)
Background: Reproductive morbidity encompasses obstetric morbidity, gynecological morbidity & contraceptive morbidity but still maternal mortality is only indicator for women's health even though Reproductive morbidity occurs far more frequently & seriously affects women's lives. Objectives: To assess the prevalence of various Gynaecological Morbidities & determinants among the women of reproductive age group in urban slums of Bhavnagar city. Materials & Methods: Community based cross sectional study was carried out by using multistage sampling method. A total of 750 women in the reproductive age group of 15 to 49 years (excluding currently pregnant) were interviewed using a pre-tested structured Performa. Results: The prevalance of Gynaecological Morbidities among study group was 45.1%, with majority having symptoms suggestive of Reproductive Tract Infections (RTI) (26.4%) & menstrual problems (26%). Among RTI, vaginal discharge (20.7%) was the most frequently encountered symptom. Education & marital status of women had shown significant influence on the occurrence of vaginal discharge (p<0.05) while socio-economic status failed to show any association. Conclusion: Vaginal discharge was the most common gynaecological morbidity which is influenced by education & marital status. Hence sex counselling & reproductive health education is essential for the women to improve reproductive hygiene.